Strategies to reduce the energy content of foods pre-ordered for lunch in the workplace: a randomised controlled trial in an experimental online canteen - Sarah Breathnach; Phillippa Lally; Clare H. Llewellyn; Alex Sutherland; Dimitrios A. Koutoukidis (BMC, 2022)
Abstract Background Prompting employees to swap their usual lunches for lower-energy alternatives may help align energy intake with public health recommendations. We tested the effect of offering lower-energy swaps with and without physical activity calorie equivalent (PACE) information on the energy of lunches pre-ordered in an online hypothetical workplace canteen. Methods UK employed adults (n = 2,150) were invited to hypothetically pre-order their lunch from the canteen through a custom-made online platform. They were randomised 1:1:1 to: (i) control: no swaps offered; (ii) lower-energy swaps offered; or (iii) lower-energy swaps offered with PACE information. The primary outcome was the total energy ordered using analysis of covariance and controlling for the energy content of the initial items ordered. Secondary outcomes were swap acceptance rate and intervention acceptability. Results Participants were 54% female, had a mean age of 36.8 (SD = 11.6) and a BMI of 26.3 (SD = 5.6). Compared with an average 819 kcal energy ordered in the control, both the swaps and swaps + PACE interventions significantly reduced average energy ordered by 47 kcal (95% CI: -82 to -13, p = 0.003) and 66 kcal (95% CI: -100 to -31, p < 0.001), respectively. Compared with offering swaps only, the swaps + PACE intervention led to significantly higher swap acceptance (OR: 1.63, 95% CI: 1.27 to 2.09, p < 0.001) but did not significantly reduce energy ordered (-19 kcal, 95% CI: -53 to 16, p = 0.591). About 65% and 16% of intervention participants found the swap interventions acceptable and unacceptable, respectively, with the swaps + PACE intervention being considered more acceptable than swaps only (OR: 1.32, 95%CI: 1.09 to 1.60, p < 0.004). Conclusion Offering lower-energy swaps with or without PACE information reduced the energy of pre-ordered lunches experimentally. Both interventions hold promise for reducing the energy of purchased foods and drinks. Trial Registration As Predicted reference number: 56358, 22/01/21, https://aspredicted.org/pw2qr.pdf